Degradation Analysis of Long-Term Solid Oxide Fuel Cell Stacks with Respect to Chromium Poisoning in La0.58Sr0.4Co0.2Fe0.8O3−δ and La0.6Sr0.4CoO3−δ Cathodes. Issue 10 (12th October 2021) - Fang, Qingping; Menzler, Norbert H.; Blum, Ludger
Abstract : Chromium poisoning as a result of Cr evaporation from the metallic components and the subsequent deposition on the cathode (i.e., air) side is one of the most critical degradation mechanisms in solid oxide fuel cell (SOFC) stacks. Recently, the LSC cathode (i.e., La0.6 Sr0.4 CoO3− δ ) exhibited more promising results in both fuel cell and electrolysis modes than the LSCF (i.e., La0.58 Sr0.4 Co0.2 Fe0.8 O3− δ ) due to its higher ionic conductivity, despite a relatively high thermal expansion coefficient (TEC). Furthermore, it has been reported that the oxygen surface exchange kinetics and Sr stability/activity in LSC may imply higher resistance against Cr poisoning in comparison to LSCF. For these reasons, long−term stack operation with both LSCF and LSC cathodes was performed for two different stack designs. The degradation behavior of the stacks with respect to Cr poisoning was analyzed with the support of electrochemical impedance spectroscopy and post-mortem analysis.